Transformational leadership and project success: the mediating roles of team reflexivity and project team resilience - Han, Huibin; Ma, Chihao; Yang, Danning; Zhao, Weiwei (Frontiers in Psychology, 2025)
Drawing from social cognitive theory, this study examines the mediating roles of team reflexivity and project team resilience in translating transformational leadership into project success. Data were collected from 261 project team members across various construction firms in China. The findings reveal that transformational leadership demonstrates a direct positive influence on project success. Moreover, transformational leadership significantly enhances both team reflexivity and project team resilience, which in turn contribute to project success. Furthermore, the results indicate that team reflexivity and project team resilience mediate the relationship between transformational leadership and project success. Based on these results, theoretical implications and practical recommendations are provided.